Jean des Murs's quadrivial pursuits: introduction - Nothaft, C; Desmond, K; Husson, M (Brill, 2019)
This is article serves as the introduction to a special issue on the intellectual activities of Jean des Murs, a mathematician, astronomer-astrologer, and music theorist active in France in the first half of the fourteenth century.